Recommendations for Plankton Measurements on OceanSITES Moorings With Relevance to Other Observing Sites - Emmanuel Boss; Anya M. Waite; Johannes Karstensen; Tom Trull; Frank Muller-Karger; Heidi M. Sosik; Julia Uitz; Silvia G. Acinas; Katja Fennel; Ilana Berman-Frank; Sandy Thomalla; Sandy Thomalla; et al. (Frontiers in Marine Science, 2022)
Measuring plankton and associated variables as part of ocean time-series stations has the potential to revolutionize our understanding of ocean biology and ecology and their ties to ocean biogeochemistry. It will open temporal scales (e.g., resolving diel cycles) not typically sampled as a function of depth. In this review we motivate the addition of biological measurements to time-series sites by detailing science questions they could help address, reviewing existing technology that could be deployed, and providing examples of time-series sites already deploying some of those technologies. We consider here the opportunities that exist through global coordination within the OceanSITES network for long-term (climate) time series station in the open ocean. Especially with respect to data management, global solutions are needed as these are critical to maximize the utility of such data. We conclude by providing recommendations for an implementation plan.